Book self : the reader as writer and the writer as critic - Stead, C. K. (Christian Karlson), 1932- (Auckland University Press, 2012)
A sequel to the successful books Kin of Place and The Writer at Work, this collection of critical writing takes the reader on a personal journey from the author's earliest discovery of poetry as a young man to his latest experiences on the literary trail. This trip through literary history involves many writers, including Katherine Mansfield, T.S. Eliot, Michael King, and Elizabeth Knox. The book also includes a series of journal extracts that allow readers to get closer to the mind of the writer, his strong personal views about other writer.